LINGUISTIC PERIPHRASIS (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article is devoted to periphrasis, which are important tool in language that enriches communication, adds depth to expression, and improves understanding. A periphrasis is one of the tools for communication and the use of linguistic periphrasis boosts expressiveness to our conversation and written texts. In this article, I will delve into the significance of linguistic periphrases and highlight their role in enhancing communication.